The homicide circumplex: a new conceptual model and empirical examination. Issue 4 (30th October 2018) - DeLisi, Matt; Drury, Alan; Elbert, Michael
Abstract : Purpose: Homicide is the most severe form of crime and one that imposes the greatest societal costs. The purpose of this paper is to introduce the homicide circumplex, a set of traits, behaviors, psychological and psychiatric features that are associated with greater homicidal ideation, homicidal social cognitive biases, homicide offending and victimization, and psychopathology that is facilitative of homicide. Design/methodology/approach: Using the data from a near population of federal supervised release offenders from the Midwestern USA, ANOVA, multinomial logistic, Poisson and negative binomial regression models were developed. Findings: Greater homicidal ideation is associated with homicide offending, attempted homicide offending and attempted homicide victimization and predicted by gang activity, alias usage, antisocial personality disorder and intermittent explosive disorder. These behavioral disorders, more extensive criminal careers, African American status and gang activity also exhibited significant associations with dimensions of the homicide circumplex. Originality/value: Developing behavioral profiles of offenders that exhibit homicidal ideation and behaviors are critical for identifying clients at greatest risk for lethal violence. The homicide circumplex is an innovation toward the goal that requires additional empirical validation.